2012
DOI: 10.1134/s1070428012010150
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic cycloaddition of diazoalkanes with heterocyclic substituents to fullerene C60

Abstract: Methanofullerenes were directly synthesized under mild conditions by cycloaddition to fullerene C 60 of diazoalkanes generated in situ by oxidation of ketone hydrazones containing a heterocyclic fragment with manganese(IV) oxide in the presence of the catalytic system Pd(acac) 2 -2 PPh 3 -4 Et 3 Al.Methanofullerenes available via Bingel-Hirsch reaction constitute now one of the most promising classes of fullerenes from the view point of practical applications. Methanofullerenes can be used in the manufacture o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 17 publications
1
13
0
Order By: Relevance
“…Now we have found that they also did not react with phenylsulfonyl isothiocyanate bearing a strong electron acceptor substituent. Indeed, 3-methyl-, 3-phenylsulfonyl-, and 3-phenylazolo [5,1-d] [1,2,3,5]tetrazine-4(3H)-thiones of type 6 could not be prepared in the same way as their oxygen analogs. In contrast to the reactions with methyl-and phenyl isothiocyanate the analogous reactions of diazoazoles 2bej with isothiocyanates containing carbonyl groups, such as ethoxycarbonyl isothiocyanate 4a, benzoyl isothiocyanate 4b and tetrafluorobenzoyl isothiocyanate 4c occur readily in solution of anhydrous ethyl acetate to give azolo [5,1-d] [1,2,3,5]thiatriazines 5 as the only products (Scheme 3, Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Now we have found that they also did not react with phenylsulfonyl isothiocyanate bearing a strong electron acceptor substituent. Indeed, 3-methyl-, 3-phenylsulfonyl-, and 3-phenylazolo [5,1-d] [1,2,3,5]tetrazine-4(3H)-thiones of type 6 could not be prepared in the same way as their oxygen analogs. In contrast to the reactions with methyl-and phenyl isothiocyanate the analogous reactions of diazoazoles 2bej with isothiocyanates containing carbonyl groups, such as ethoxycarbonyl isothiocyanate 4a, benzoyl isothiocyanate 4b and tetrafluorobenzoyl isothiocyanate 4c occur readily in solution of anhydrous ethyl acetate to give azolo [5,1-d] [1,2,3,5]thiatriazines 5 as the only products (Scheme 3, Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…In summary, we have developed an efficient method for the synthesis of imidazo-and pyrazolo [5,4-b] [1,2,3,5]thiatriazines based on cycloaddition reaction of diazoazoles with acyl isothiocyanates. The prepared compounds are shown by both X-ray data for thiatriazines 5k,l and by calculations for the structures 5k,l,o to have relatively strong SeO nonbonded interactions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations